In search of Sustainability of the Sugarcane Crop and Sugar Industry: The Role of Preparation and Training of Human Resources - Milanés-Ramos, N.; Castillo-Morán, A.; Rodríguez-Lagunes, D. A.; Herrera-Solano, A.; Sarquís, H. Ortiz Romero J. I. (International Journal of Bio-resource and Stress Management, 2023)
Universidad Veracruzana, Mexico is well known in the Mexican state with the highest sugar production of the country. Therefore, in recent times Universidad Veracruzana began focusing on social, cultural and technological aspects of this significant agro-industry of Veracruz in particular and Mexico as a whole. The Institute for the Improvement of Sugar Production (IMPA), founded in 1949, was the institution that sponsored research in this area, but the entity was terminated in 1990. This event was the main single event that led Universidad Veracruzana, jointly with other research centers, to initiate a program dedicated to train professionals for the sugarcane industry in Mexico. Eleven of the sugar factories in the state are located in the region of Cordoba, where the MS Program ‘Management and Use of Sugar Cane Agricultural Systems’ was started in 1995. Nine of our graduates are working in sugar mills within the Cordoba region. This paper presents the characteristics of the cited MS Program and its relationship to the sugar agro-industry of Veracruz through research projects and technological improvement. It also presents some of the results from the research done; all this with the purpose of showing that the essential goal of the program is the preparation of highly trained human resources for the sugarcane industry.